Analisis Pemanfaatan Komoditi Kelapa Sawit terhadap Produk Domestik Regional Bruto (PDRB) Sub Sektor Perkebunan dengan Memperhatiakn Aspek Lingkungan di Provinsi Kalimantan Selatan - Fadjar Geuvara Tanmaela; Muhammad Anshar Nur (PPJP Universitas Lambung Mangkurat, 2022)
This research was conducted to determine how much influence the Oil Palm Commodity has on GRDP growth, especially in the Plantation Sub-Sector in South Kalimantan Province, and to find out how much influence oil palm has on the environment so that it calculates the Green GRDP.Data was collected from various sources, including the Central Bureau of Statistics, NASA aerospace, Bank Indonesia, the Intergovernmental Panel on Climate Change, NOAA, World Wildlife Fund (WWF) , Greenpeace, the Palm Oil Association, BBC, PT. Perkebunan Nusantara 5. This research uses the calculation of Depletion, Environmental Degradation, and Depreciation which is used to identify the amount of value to be obtained by Green GRDP, which is expected to contribute and in line with the enactment of Government Regulation No. 46 of 2017 concerning Environmental Economic Instruments.This study finds that the Sub-Sector of Oil Palm Commodity Plantation is sufficient to contribute to the value of conventional GRDP in South Kalimantan Province. The implementation of Green GRDP is expected to be implemented in every district / city in South Kalimantan Province in order to create a sustainable use of natural resources.